1981
DOI: 10.1002/path.1711330305
|View full text |Cite
|
Sign up to set email alerts
|

Plasma transferable inhibition of BCG induced subcutaneous inflammation in human cancer

Abstract: When a small dacron sponge disc containing live BCG was implanted subcutaneously in healthy subjects it became infiltrated with leukocytes which at 24 hours mainly involved neutrophils. this mycobacterial-induced inflammatory response was markedly impaired in patients with cancer. This inhibitory effect could be reproduced by injecting the plasma of these patients into guinea-pigs bearing identical discs. The differences in inflammatory reactions in the indirect technique were less marked than in the direct te… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

1986
1986
1992
1992

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(2 citation statements)
references
References 26 publications
0
2
0
Order By: Relevance
“…Granulocytes are present in large numbers in inflammatory reactions and their number also are increased in chronic inflammatory diseases. However, the cellular inflammatory response is depressed in animals bearing malignant tumors (1,2) and in patients with all types of malignancies studies so far (3,4). In previous work with the guinea-pig, we showed that ketoprofen administration restored the BCG-induced migration of leukocytes that was reduced by injection of plasma obtained from cancer patients (5).…”
Section: Introductionmentioning
confidence: 91%
“…Granulocytes are present in large numbers in inflammatory reactions and their number also are increased in chronic inflammatory diseases. However, the cellular inflammatory response is depressed in animals bearing malignant tumors (1,2) and in patients with all types of malignancies studies so far (3,4). In previous work with the guinea-pig, we showed that ketoprofen administration restored the BCG-induced migration of leukocytes that was reduced by injection of plasma obtained from cancer patients (5).…”
Section: Introductionmentioning
confidence: 91%
“…The migration of leukocytes was studied using the in vivo migration test developed in our laboratory [9]. Briefly, a disk of sterilized mesh material made of rayon (obtained from Ethnor, France) was implanted subcutaneously in ether-anesthetized mice.…”
Section: Study Of the Leukocyte Migrationmentioning
confidence: 99%